Validation of Instrument to Measure Science Pre-Service Teachers Digital Skills: Confirmatory Factor Analysis - Ningthias, Dyah Pusptasari; Qudratuddarsi, Hilman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Validating instruments that measure digital skills—such as through Confirmatory Factor Analysis (CFA)—is crucial to ensure that pre-service teachers, particularly those from Generation Z, possess accurate, reliable, and pedagogically meaningful digital competencies. Using a quantitative survey design, data were collected from 349 Generation Z pre-service teachers across four science specializations (chemistry, physics, biology, and general science). The instrument used was adapted from previous studies and translated using the back-translation method to ensure its validity. Confirmatory Factor Analysis (CFA) was employed in AMOS 24 to evaluate both first-order and second-order models to analyze the data. The six dimensions assessed—Access to and Management of Digital Content (AMDC), Use of Digital Means (UDM), Communication Skills (CS), Creative Skills (CrS), Digital Safety Skills (DSS), and Digital Empathy (DES)—demonstrated strong loadings onto the higher-order construct of Digital Skills (standardized regression weights = 0.94–0.97). Model fit indices confirmed the robustness of the structure (χ² = 865.079, RMSEA = 0.075, TLI = 0.908, CFI = 0.923). Reliability was high, with Cronbach’s alpha ranging from 0.674 to 0.966 and Composite Reliability (CR) exceeding 0.70 for most constructs. Correlation analysis revealed strong interrelationships among dimensions (r = 0.779–0.998), underscoring the integrated nature of digital skills. The findings suggest that digital skills among pre-service science teachers can be conceptualized as a unified but multidimensional construct. The validated instrument offers a reliable tool for assessing digital competencies in teacher education. Practically, the results have implications for curriculum development, underscoring the need to integrate digital literacy training into teacher preparation programs. Future research should expand validation to diverse cultural contexts and apply longitudinal approaches to capture changes in digital skill development over time.